NEONATAL GRAVES’ DISEASE: AN UNUSUAL METABOLIC AND CARDIAC ASSOCIATION FROM PRESENTATION TO RESOLUTION - Ramachandran, Puvanesvaran; Idris, Arini Nuran; Pian Pian, Tee; Inaz, Farah; Ling, Lilian Ngo Ping; Alias, Amelia; Chen, Kam Choy; Giok, Lim Poi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Neonatal Graves’ disease is a rare disorder seen in 1 in 25000 births, caused by transplacental passage of TSH receptor antibody. Despite serious potential multisystem complications, it can be transient. METHODOLOGY We describe a newborn born to a mother with undiagnosed Graves’ disease. RESULTS A male neonate was born prematurely at 31-weeks gestation via emergency lower segment caesarean for fetal distress with a birth weight of 1.7 kg. He was admitted to the neonatal intensive care unit due to respiratory distress requiring non-invasive ventilation. Newborn examination revealed hepatosplenomegaly with conjugated hyperbilirubinemia, hence, he was empirically treated for congenital infections. At 72 hours, the patient developed tachycardia and further work up resulted in suppressed cTSH. At that time mother was incidentally noted to have features of clinical Graves’ disease which was confirmed by 2 thyroid function tests and positive TSH receptor antibody. Further radiological assessment of the newborn revealed periportal fibrosis and pulmonary hypertension. He was commenced on carbimazole and short course of prednisolone which resulted in resolution of hyperthyroidism, pulmonary hypertension, periportal fibrosis and thrombocytopenia. CONCLUSION Pulmonary hypertension and periportal fibrosis are rare clinical manifestations of neonatal Graves’ disease which are reversible with resolution of hyperthyroidism.